Peer Review - Professional Doctor Mistakes And Verdicts Judge: Dilemma In Medical Services In Indonesia - Triono Eddy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Professional Doctor Mistakes And Verdicts Judge: Dilemma In Medical Services In Indonesia